ANALYSIS OF THE INFLUENCE OF INFLATION, EXPORT VALUE, IMPORT AND INVESTMENT ON INDONESIA'S ECONOMIC GROWTH AND PERCAPITA INCOME IN 2023: PANEL DATA REGRESSION APPROACH - Suhari Suhari; Hwihanus Hwihanus; Slamet Riyadi (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
This study analyzes the impact of inflation, trade, and investment on Indonesia's economic growth and purchasing power (1990-2022). Using panel data regression, we find: that inflation and exports have a positive impact on both GDP and purchasing power. Inflation boosts aggregate demand while exports increase income. Imports have a positive impact on purchasing power due to the increased availability of goods, but a negative on GDP due to potential trade imbalances. Domestic and foreign investment hurt both GDP and purchasing power. While investment boosts production, it can also intensify competition, leading to price reductions and dampened purchasing power. The findings of this study have implications for policymakers in Indonesia. Policymakers should focus on policies that can promote inflation, exports, and foreign direct investment. These policies can help to increase purchasing power and improve the standard of living of Indonesians